Should we take anodyspareunia seriously? A descriptive analysis of pain during receptive anal intercourse in young heterosexual women - Štulhofer, Aleksandar (Array, 2011)
Anal sex is becoming increasingly prevalent among heterosexual women and men. Although pain related to receptive anal intercouse is not uncommon, little is known about its phenomenology. The article aims to assess the prevalence and correlates of pain during anoreceptive intercourse, including anodyspareunia, its most severe form, among young women. An online survey focusing on anal eroticism was carried out in March and April 2010 on a convenience sample of 2, 002 women 18-30 years of age. Participants who reported 2 or more episodes of anal intercourse in the past years were asked about the level and frequency of pain at anoreceptive penetration ; those who reported unbearable (too painful to continue) or strong pain at every such occasion were classified as anodyspareunic. The experience of anal intercouse was reported by 63.2% (n=1, 265) of participants. Although almost half (48.8%) had to discontinue their first anoreceptive intercourse because of pain or discomfort, a majority of women (62.3% ; n=788) continued anal sex. Of the 505 participants who reported 2 or more episodes of anal intercourse in the past year, the women (8.7% ; n=44) who reported severe pain during every anoreceptive penetration were classified as non-anodyspareunic. For more than two thirds of women with anodyspareunia, the current pain level remained unchanged from their first experience with anal sex. Inability to relax was the most frequent self-hypothesized cause of pain among the anodyspareunic and nonanodyspareunic groups. Compared with other women, those with anodyspareunia reported substantially lower levels of sexual satisfaction (odds ratio=.95 ; p<.001) and were less sexually assertive (odds ratio=.80 ; p<.01). The findings that a substantial proportion of women reported pain at first and subsequent anoreceptive intercourse highlight a need for more information and education about anal eroticism.